Into the heart of the Mandaya [videorecording] a journey through the milds of Davao Oriental - Medina, Susan Calo.; Quintos, Floy.; GMA 7 (Television station : Quezon City, Philippines).; Philippines. Department of Tourism; Travel Time (Television program). (Manila Travel Time, 1995)
Features the Mandayas, the indigenous cultural minorities in Davao Oriental.
Documentary.
VHS.
Keywords: Mandayas; Mandayas -- Social life and customs; Davao Oriental (Philippines) -- Description and travel; Davao Oriental (Philippines) -- History